Prognosis of Preschool Eczema and Factors of Importance for Remission - Emma Kristin Johansson; Anna Bergström; Inger Kull; Tomas Lind; Cilla Söderhäll; Erik Melén; Samina Asad; Maria Bradley; Agne Liedén; Natalia Ballardini; Carl-Fredrik Wahlgren (Medical Journals Sweden, 2018)
Information on factors of importance for remission of eczema is scarce. This study explored factors related to the remission and course of preschool eczema (PSE) (eczema at 1, 2 and/or 4 years of age) to 16 years of age (n = 889) in a Swedish cohort. Half of the children were in complete remission by school age (at age 8, 12, and 16 years). In multivariate prognostic models, persistent PSE (eczema at 1, 2 and 4 years of age) (odds ratio 0.27 (95% confidence interval 0.18-0.41)), PSE with sleep disturbance (due to itch at least once a week at 1, 2 and/or 4 years of age) (0.59 (0.43-0.81)), parental allergy (0.73 (0.55-0.96)), parental smoking at child's birth (0.70 (0.50-0.99)) and filaggrin mutation (R501X, R2447X, 2282del4) (0.47 (0.26-0.85)) were inversely associated with complete remission by school age. Male sex (1.37 (1.03-1.82)) and exclusive breastfeeding ≥4 months (1.44 (1.01-2.05)) were positively associated with complete remission by school age. In conclusion, half of the children with PSE were in complete remission by school age. The most important prognostic factors were persistent PSE and PSE with sleep disturbance due to itch.